Variación de los ingresos en la Empresa Coeriego S.A., del Cantón Vinces de la provincia de Los Ríos en los periodos 2021 - 2022. - Fajardo Navarrete, Rossi Estefani (2024)
This case study was carried out in the company COERIEGO S.A. in the city of Vinces in the province of Los Ríos, its objective is to evaluate and analyze the variations in income that occurred in the periods 2021 and 2022, in turn allowing us to detail the negative impact that these changes have had and how it has affected in its liquidity. In order to carry out this work, a mixed approach was used, which was able to obtain qualitative and quantitative data where the problems presented by this organization could be observed from different points and allowed us to determine different strategies that can benefit the company COERIEGO S.A. in the long term and can have a positive respite in the future. Carrying out a horizontal analysis helped to clearly and accurately analyze the income that COERIEGO S.A. had. on a monthly and semi-annual basis, which led to visualizing which months in 2022 their sales decreased compared to 2021, in addition to applying an internal control questionnaire, it was possible to analyze the precision and efficiency of the different strategies implemented by the organization.